Unraveling the Determinants of Budgetary Slack: A Study of Participation, Information Asymmetry, and Organizational Factors - Yenny Verawati; Ni Wayan Rustiarini (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: Budgeting is not just a financial plan to monitor expenses and revenues over time within an organization; it also serves as an essential management tool for executing the company’s strategic goals. This study seeks to examine how factors such as budget participation, information asymmetry, self-interest, role ambiguity, and organizational commitment affect budgetary slack at Village Credit Institutions (LPD) in Denpasar City. Methodology: Using purposive sampling, responses were collected from 136 participants, the subjects comprised 34 various LPDs in Denpasar, Bali Indonesia. The researchers used a purposive sampling approach in selecting participants. Through specified inclusion criteria, 136 individuals were selected as responders—34 LPD heads, 34 heads of the credit department, 34 cashiers, and 34 internal supervisory team members. The individuals were selected because of the immediate involvement and knowledge of budgetary preparations in these institutions. The data analysis was performed using multiple linear regression on SPS software. Findings: The findings indicate that budget participation, information asymmetry, self-interest, role ambiguity, and organizational commitment all positively influence budgetary slack in LPDs in Denpasar City. Implications/Novel Contribution: To improve the prediction of factors affecting budgetary slack, future studies should consider including additional variables, such as leadership style and internal control systems. This study brings useful lessons for financial institutions and policy makers.